Penerapan Model Epidemic Type Aftershock Sequence (ETAS) pada Data Gempa Bumi Jawa Barat - Sofi Sopiah; Sutawanir Darwis (Bandung Conference Series: Statistics, 2024)
Abstract. Earthquake intensity mapping is an important step in mitigating the risk of natural disasters, especially earthquakes. Earthquake activity is still being studied from both seismological and stochastic aspects. One of the stochastic processes that can explain earthquake activity is the point process. The point process is a stochastic process that can explain natural phenomena that are random in both space and time. One of the models in the point process is the epidemic type aftershock sequence (ETAS) model. The ETAS model is expressed by a conditional intensity function that is useful for knowing the chances of earthquake occurrence. Therefore, the purpose of this study is to apply the ETAS model to earthquake data in West Java. Data obtained from the United State Geological Survey (USGS) was declustered with the Gardner Knopoff method and there were 49 clusters and took 1 cluster with the largest earthquake data, namely the earthquake on September 02, 2009 in Tasikmalaya. The maximum likelihood estimation method is used to obtain parameter estimates of the ETAS model. The null model and full model are used to show the magnitude of the exponential distribution, while the full model shows the magnitude of the gamma distribution. With the maximum likelihood method, the parameter estimates of the basic intensity function of the null model and full model were obtained. The earthquake in Tasikmalaya in 2009 obtained the best model, the full model. The results of the parameter estimation are the base seismicity rate of 0.04402, the aftershock productivity of 4.673611e-9, the efficiency of an earthquake with a certain magnitude to produce aftershocks of 59.4750, the time scale of aftershock decay rate of 0.0083, and the aftershock decay rate of 1.3825. Abstrak. Pemetaan intensitas gempa merupakan langkah penting dalam upaya mitigasi risiko bencana alam, khususnya gempa bumi. Aktivitas gempa bumi masih terus dikaji baik dari aspek seismologi maupun aspek stokastik. Salah satu proses stokastik yang dapat menjelaskan aktivitas gempa bumi adalah proses titik. Proses titik merupakan suatu proses stokastik yang dapat menjelaskan fenomena alam dimana sifatnya acak baik dalam ruang maupun waktu. Salah satu model dalam proses titik adalah model epidemic type aftershock sequence (ETAS). Model ETAS dinyatakan dengan fungsi intensitas bersyarat yang berguna untuk mengetahui peluang kemunculan terjadinya gempa bumi. Oleh karena itu tujuan penelitian ini adalah menerapkan model ETAS pada data gempa bumi di Jawa Barat. Data diperoleh dari United State Geological Survey (USGS) di decslustering dengan metode Gardner Knopoff terdapat 49 cluster dan mengambil 1 cluster data gempa bumi yang terbesar yaitu gempa pada tanggal 02 September 2009 yaitu di Tasikmalaya. Metode estimasi likelihood maksimum digunakan untuk memperoleh estimasi parameter model ETAS. Digunakan null model dan full model untuk menunjukkan magnitudo berdistribusi eksponensial, sedangkan full model menunjukkan magnitudo berdistribusi gamma. Dengan metode likelihood maksimum diperoleh estimasi parameter fungsi intensitas dasar dari null model dan full model. Gempa di Tasikmalaya pada tahun 2009 memperoleh model terbaik yaitu full model. Hasil estimasi parameter tersebut yaitu laju kegempaan dasar sebesar 0.04402, produktivitas gempa susulan sebesar 4.673611e-9, efisiensi gempa bumi dengan magnitudo tertentu menghasilkan gempa susulan sebesar 59.4750, skala waktu laju peluruhan gempa susulan sebesar 0.0083, dan laju peluruhan gempa susulan sebesar 1.3825.